Male and Female Students’ Preferences on the Oral Corrective Feedback in English as Foreign Language (EFL) Speaking Classroom - Hawin Amalia, Zaky Dzulhiza; Fauziati, Endang; Marmanto, Sri (Bina Nusantara University, 2019)
This research aimed at investigating the male and female students’ preferences on the six types of Oral Corrective Feedback (OCF). This qualitative research used observation and interview to collect data. The observation was done to know the practice of the six types of OCF in speaking class and the interview was conducted to reveal the students’ preferences for OCF. The result from the observation shows that the lecturer mostly uses Explicit Correction to correct the students’ error. Then, the result from the interview indicates that male students prefer to have Explicit Correction because this type is the easiest type to know the error and correction clearly. Whereas the female students prefer to have Recast and Metalinguistic Feedback because Recast does not encourage them and Metalinguistic Feedback can make them think critically under the lecturer’s clue. Subsequently, both male and female students perceive Clarification Request and Repetition as the ambiguous type to grasp what the lecturer’s mean. The result of this current research is expected to provide an additional information about the practice of OCF strategies in speaking classroom which is appropriate with the students’ preferences.